Kaempferol and kaempferol glycosides from Phyllanthus acidus leaves - Thuy Tram, Nguyen Cong; Son, Ninh The; Thao, Do Thi; Cuong, Nguyen Manh (Vietnam Journal of Chemistry, 2016)
In the search for hepatoprotective plants in Vietnam, the leaves of Phyllanthus acidus (L.) Skeels were selected for chemical investigation. Phytochemical analysis of the ethyl acetate fraction of the methanol extract led to the isolation of four compounds, including kaempferol (1), and its glycosides, kaempferol-3-O-β-D-glucoside (2), kaempferol-3-O-α-L-rhamnopyranoside (3), and kaempferol-3-O-α-L-rhamnopyranosyl-(1®2)- α-L-arabinopyranoside (4). The structures of the natural compounds were determined from the spectroscopic evidences, including 1D, 2D-NMR. Here is the first report of the isolation of compound 4 from the genus Phyllanthus, family Phyllanthaceae.